Replacement versus adaptation investments and equity value - Nwaeze, Emeka T. (Journal of Corporate Finance, 2005)
I examine the relative effects of replacement investments (RX) and adaptation investments (AX) on equity value. My analysis draws from the real-options theory that stresses the link between firm value and the option a firm holds to continue current practice or to adapt resources to new opportunities. The key prediction is that replacement and adaptation investments reflect the exercise of different investment options that have different implications for firm value; the effect of each investment type on firm value depends on the relative attractiveness of the underlying investment option. The results show that, in the presence of earnings, the effect of replacement investments on equity value is negative and increasing in earnings performance; by contrast, the effect of adaptation investments on equity value is positive and decreasing in earnings performance. Further analyses show that asset sales mediate the importance of adaptation investments in determining equity value.